The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1101/2020.06.16.20126466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Syndromic surveillance insights from a symptom assessment app before and during COVID-19 measures in Germany and the United Kingdom: results from repeated cross-sectional analyses

Abstract: Background: Unprecedented lockdown measures have been introduced in countries across the world to mitigate the spread and consequences of COVID-19. While attention has focused on the effects of these measures on epidemiological indicators relating directly to the infection, there is increased recognition of their broader health implications. However, assessing these implications in real time is a challenge, due to limitations of existing syndromic surveillance data and tools. Objective: To explore the added va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…CDSS facilitating clinical decision-making have exhibited strong performance in several previous studies, including the Ada-App 8,9,19–23. Gilbert et al10 recently evaluated the performance of eight digital symptom assessment apps, showing that Ada achieved a higher accuracy (71%) in comparison to other apps for the top 3 diagnoses (average: 47%), providing safe urgency advice in 97%.…”
Section: Discussionmentioning
confidence: 99%
“…CDSS facilitating clinical decision-making have exhibited strong performance in several previous studies, including the Ada-App 8,9,19–23. Gilbert et al10 recently evaluated the performance of eight digital symptom assessment apps, showing that Ada achieved a higher accuracy (71%) in comparison to other apps for the top 3 diagnoses (average: 47%), providing safe urgency advice in 97%.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies in Europe and Asia have found that self-reported symptoms collected through mobile applications had strong spatial correlations with confirmed COVID-19 cases 5 and that by collecting data before and after COVID-19 restrictions, the tool was effective in evaluating control measures. 6 In April 2020, C19Check.com (C19Check) was launched by Emory University and Vital Software Inc. in Atlanta, Georgia (GA). The online symptom tracker, freely available in 31 languages, prompts users to report their symptoms and then generates evidence-based summaries of risk of COVID-19 infection and advice for seeking healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of error in the forecast is likely because C19Check use itself is not a cause of the surges and declines in cases and hospitalizations. The significant results for all time-lags tested indicate that our findings on the predictability of C19Check use were not impacted by time-lags, demonstrating the effectiveness of C19Check as a tool for syndromic surveillance of COVID-19 cases and hospitalizations in GA. Other real-time syndromic surveillance tools have been used to detect early signals, monitor population transmission dynamics and identify hotspots in different countries 5,6,9,10 and various regions of the US. 9,11 However, we also evaluated the performance of an internet-based self-triage tool in predicting COVID-19 cases and hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…While participatory crowdsourced syndromic surveillance has been utilized in many contexts [1]–[7], including for COVID-19 [8], [9], their ability to track an emerging outbreak at a high spatial resolution has not been evaluated previously. Here, we show that one such system, though noisy, provides an indication of where and when to expect new cases, suggesting that it could be a useful model in other places that need to map COVID-19 risk for decision making.…”
Section: Introductionmentioning
confidence: 99%